Employee motivation an Islamic perspective - Bhatti, Omar K.; Aslam, Uzma S.; Hassan, Arif; Sulaiman, Mohamed (Emerald Group Publishing Limited, 2016)
Purpose – This paper aims to provide an understanding of employee motivation from the Islamic perspective. The main objective of this paper is to understand Islamic motivation and to explore if Islamic spirituality, punishment and reward and justice motivate Muslim employees. Design/methodology/approach – Qualitative research approach was used to understand and examine the views of the respondents. Semi-structured interviewing technique was adopted, and the respondents were asked to share their own thoughts and understanding for each question provided. A sample of 13 experienced academicians and practitioners from renowned private organizations and academic institutions from Malaysia and Pakistan were selected for the present study. Findings – The study found that the conventional viewpoint of motivation varies from Islamic viewpoint in regard to motivation of employees. And significantly, Islamic spirituality, reward and punishment, and justice act more compellingly in improving employee’s motivation. Originality/value – This paper clearly highlights that the Western viewpoint of employee motivation is different as compared to the Islamic perspective.